Hubungan Kesehatan Mental pada Ibu Nifas dengan Tingkat Pengeluaran ASI di Puskesmas Lewa Nusa Kabupaten Sumba Timur Tenggara Timur (NTT) - Nasrani Hamu Kabeba Niwa; Erni Nuryanti; Rafika Fajrin (Midwifery Care Journal, 2025)
The postpartum period is the period after childbirth. The postnatal phase contains several adaptations, but not all postpartum mothers can go through it well and this can have an impact on mental health. Therefore, the mental health of postpartum mothers is something that must be considered, especially postpartum mothers who are very vulnerable to baby blues and postpartum depression, considering that poor mental health in postpartum mothers can hinder the smooth flow of breast milk. The aim of this research is to determine the relationship between mental health in postpartum mothers and the level of breast milk production in the Lewa Community Health Center working area, East Sumba Regency, NTT. This research was conducted at the Lewa NTT Community Health Center with a sample size of 30 postpartum mothers on days 1 to 10. This research used a correlation analytical method with a cross-sectional design. The instruments used were the EPDS questionnaire and the breast milk flow smoothness questionnaire. Bivariate analysis used the Spearman Rank test. The results showed that 19 (63.3%) respondents experienced moderate postpartum blues, and 21 (70%) respondents experienced irregular milk production. There is a relationship between mental health and the level of breast milk production in postpartum mothers with a P-value of 0.000 (0.05). It is hoped that community health centers can increase outreach and counseling activities to provide information related to mental health and optimal health education for postpartum mothers.